The Representation of Gender in English Textbooks in Indonesia - Yonata, Fadhila; Mujiyanto, Yan (Language Circle: Journal of Language and Literature, 2017)
The urgency of revealing the actual situation of gender equality in education is the background of this study. Two textbooks used regularly in Senior High School level in Semarang namely ‗Bahasa Inggris‘ (henceforth BI) and ‗Aim High‘(henceforth AH) were used as the subjects of the study. Briefly, the objectives of the study are to describe the similarities of the representation of gender in BI and AH and to describe differences of the representation of gender in BI and AH. In gathering the data, content analysis for analyzing gender representation proposed by Brugeiilles and Cromer (2009) was used as the instrument to gain the data after being adapted in some parts. The results of the analysis revealed that (1) both BI and AH are similar in the domination of male over female in the exercise and images part; they are also similar in depicting male characters engaged with higher education, social, and outdoor-based activities. In another side, (2) Both BI and AH are different in which BI has no one female- or equal shared domination in all of the parts while AH has female dominated the frequency in the course material and equal shared domination in the reading passage and conversation part.